Study and development of methods for predicting the physical and mechanical properties of thin wire and metal cord - E. S. Eltsova; Yu. L. Bobarikin; Yu. V. Martyanov (Литьë и металлургия)
Predicting the physical and mechanical properties of thin wire and metal cord will ensure an increase in the quality of latuned thin wire, a reduction in the number and time of technological pauses, and increase the manufacturability of metal cord twisting. Considering that the deformation manifests anisotropy of the properties of thin wire, the prediction of physical and mechanical properties and the degree of unevenness of deformation becomes an urgent task.The paper studies that an increase in the drawing speed of a thin wire leads to the acquisition of a more uniform and fine‑grained structure. The dependences of the physico‑mechanical properties of thin latuned wire after the metal cord is twisted on the speed of fine drawing are developed. The effect of the deformation rate on the microhardness of a thin steel wire is investigated. It is determined that in order to increase the productivity of metal cord twisting, it is necessary to bring the dependence of the increase in hardness and equivalent stresses in metal cord wires to a linear form by changing the speed of the twisting at its individual stages. For practical use, the dependences of the mechanical properties of a thin wire of strength class HT on the drawing speed are derived.During the analysis, the results were obtained, which are applicable in the design of new or modification of existing routes for drawing thin wire, as well as in the design of new metal cord structures.